2016
DOI: 10.1007/s40503-016-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Does the commodities boom support the export led growth hypothesis? Evidence from Latin American countries

Abstract: Commodity prices are characterized by boom and bust cycles. In this article, the impact of the commodity boom of the 2000s on Latin American and Caribbean economies is studied by analyzing four categories of commodity exports (agricultural raw materials, fuel, food, ore and minerals) as well as manufactured exports. Latin American and Caribbean economies had higher growth during the 2000s than in the period before the commodities boom. This study examines whether the higher growth was explained by the commodit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…More specifically, Yang (2008) showed that at the time of high economic growth, from 81 countries observed, 70 of them experienced higher export growth than GDP growth. Next, the study on exports and economic growth focused much on exportled growth hypothesis, be it at crosscountries levels, and at regional levels such as Latin America and Caribean (Kristjanpoller et al, 2016) or at an individual country level such as Bosupeng (2015) for Botswana.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Yang (2008) showed that at the time of high economic growth, from 81 countries observed, 70 of them experienced higher export growth than GDP growth. Next, the study on exports and economic growth focused much on exportled growth hypothesis, be it at crosscountries levels, and at regional levels such as Latin America and Caribean (Kristjanpoller et al, 2016) or at an individual country level such as Bosupeng (2015) for Botswana.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Le and Bao (2019) and Santiago et al (2020) found that energy use has a positive impact on LAC economic growth. In general, natural resources and energy endowments are important growth drivers for the LAC economies (Kristjanpoller et al 2016;Zeeshan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, both are important growth drivers for the LAC economies (Kristjanpoller et al 2016;Le and Bao 2019;Zeeshan et al 2020). The main evidence on the LAC region seems to contradict the NRCH since several works found no evidence that supports this hypothesis (Haber and Menaldo 2012;Blanco and Grier 2012;Toscani 2017;Papyrakis and Pellegrini 2019;Azam 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The study showed little evidence of such asymmetry by applying the standard linear and nonlinear dynamic models. Kristjanpoller et al (2016) used the dynamic ordinary least squares (DOLS) approach to study Latin American and Caribbean economies. Findings from the study indicated that natural resources and agricultural exports adversely impacted economic prosperity during booms.…”
Section: Empirical Reviewmentioning
confidence: 99%